2018
DOI: 10.1371/journal.pone.0198638
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting psychological well-being: Evidence from two nationally representative surveys

Abstract: Financial status is thought to be an important determinant of psychological well-being. We investigate this relationship, and the effect of other factors, using a parametric mixed modelling approach for panel data, controlling the problem of unobservable heterogeneity.Two nationally representative surveys, the British Household Panel Survey (BHPS) and the Understanding Society Survey (USS), were used to construct a unified data set which measured psychological well-being and associated factors using the 12-ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 32 publications
6
38
0
1
Order By: Relevance
“…Even though the results presented in this systematic review showed no difference between income level of the countries and CMD, further studies with this focus are needed in order to deepen the knowledge about the subject. Longitudinal studies such as the British Household Panel Survey (BHPS) and Longitudinal Study of Young People in England (LYSPE) demonstrate the impact of economic recession and poverty in populations by strong associations between socioeconomic variables and health outcomes [76,[108][109][110][111].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the results presented in this systematic review showed no difference between income level of the countries and CMD, further studies with this focus are needed in order to deepen the knowledge about the subject. Longitudinal studies such as the British Household Panel Survey (BHPS) and Longitudinal Study of Young People in England (LYSPE) demonstrate the impact of economic recession and poverty in populations by strong associations between socioeconomic variables and health outcomes [76,[108][109][110][111].…”
Section: Discussionmentioning
confidence: 99%
“…The use of summary measures of inequalities, such as RII and SII, involved assessing SEPs with hierarchical indicators. We used income and education, which are among the most commonly used indicators, and perceived financial status, which is known to be a determinant of self-rated psychological well-being [ 56 ]. Comparisons between socioeconomic groups were performed by examining the overlap between confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…When zero is not included in the 95% confidence interval, one can conclude that the indirect effect of the independent variable (i.e., transformational leadership) on the dependent variable (i.e., general health) is mediated by the proposed sequential mediators (i.e., hardiness and work engagement). Based on previous empirical results, we decided to control for the potential confounding effect of participants’ gender, age, and job tenure (Garrosa et al, 2008; Harju et al, 2016; Oskrochi et al, 2018).…”
Section: Methodsmentioning
confidence: 99%